Parent Perspectives of Receiving Early Information About Palliative and End-of-Life Care Options From Their Child's Pediatric Providers. Issue 4 (July 2019) - Hendricks-Ferguson, Verna L.; Haase, Joan E.
Abstract : Background: Parents of children diagnosed with cancer may experience decision regret about cancer treatment decisions and dissatisfaction with the perceived clarity in information received from their child's providers. Objective: The aim of this study was to describe parental perspectives about receiving an early palliative care and end-of-life (PC/EOL) communication intervention titled "Communication Plan: Early through End of Life Intervention" (COMPLETE) from an interprofessional team of physician and registered nurse providers. Methods: Ten parents participated in semistructured interviews after receiving the COMPLETE intervention. The COMPLETE intervention included 3 sessions delivered shortly after diagnosis and at the next 2 cancer treatment evaluations. Sessions of COMPLETE focused on early PC/EOL care discussions at diagnosis and after tumor response evaluations with their child's providers. Results: Results included 2 theme categories: (1) COMPLETE nurtures realistic hope and meaningful dialogue by parents connecting with healthcare providers as a dyad, and (2) benefits of COMPLETE helped parents to make informed decisions. In addition, there were offered suggestions to improve COMPLETE. Conclusion: The COMPLETE intervention provided a unique mechanism to foster early discussions about PC/EOL options between parents and an interprofessional team during the first 6 months of the child's cancer treatment. Future study is needed using a randomized clinical control-group design to evaluate COMPLETE with a large sample of parents. Implications for Practice: Findings provide promising evidence of parents' preference and receptivity to receive early information about PC/EOL care options for a child with a brain tumor with a poor prognosis. The COMPLETE intervention provided a mechanism to help encourage parental consideration of realistic hoped-for goals for their child's condition and care. Abstract : Supplemental digital content is available in the text.